IMPACT OF IFRS ADOPTION ON FINANCIAL STATEMENTS VALUE RELEVANCE. A STUDY OF EASTERN VS. WESTERN EUROPEAN COUNTRIES - GIUGLEA, Antonia Cosmina (Studia Universitatis Babeș-Bolyai Oeconomica, 2023)
The implementation of IFRS has been a significant milestone in the accounting field, sparking debates among advocates and critics regarding whether the initial objectives were actually achieved in practice. This paper aims to investigate whether the adoption of IFRS has led to an increase in the value relevance of financial statements in both Eastern and Western European countries. The study takes an empirical approach, analyzing companies before and after the adoption of IFRS, and introduces contemporary concepts that can contribute to future research. Policymakers rely on evidence-based policies and often seek impartial and reliable evidence from academic researchers. Given the extensive body of research conducted thus far, this paper seeks to further emphasize the positive impact of IFRS implementation. JEL Classification: G14, G15